Experimental Study for the Influence of Operating Parameters on Copper Electrorefining Process - Abbas, Hayder M.; Najim, Sarmad T. (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Copper electrodeposition by electrorefining process in acidic sulfate media contains 40 g/l of cupric ions and 160 g/l of sulfuric acid was achieved to study the influence of the operating parameters on cathode purity, surface morphology, deposition rate, current efficiency and power consumption. These operating parameters and there ranges are: current density 200, 300 and 400 A/m2, electrolyte temperature 35, 50 and 65 oC, electrodes spacing 15, 30 and 45 mm and electrolyte residence time 6, 4 and 2 h were utilized. XRF, SEM and EDX analyses were attained to clarify the properties of the produced cathode.